Around the table that grandad built - Hill, Melanie Heuiser (Candlewick Press, 2019)
A family gathers with friends and neighbors to share a meal around a table that is full of associations of how every member contributed to the meal
Keywords: Dankbarkeit; Nahrungsaufnahme; Familie; Großvater; Enkel; Tisch; Grandfathers / Juvenile fiction; Grandparent and child / Juvenile fiction; Dinners and dining / Juvenile fiction; Nursery rhymes; Family / Fiction; Thankfulness / Fiction; Dinners and dining; Grandfathers; Grandparent and child; Picture books for children; Fiction; Juvenile works; Picture books; Bilderbuch